The impact of hotel attributes on room rate in star graded hotels in Colombo, Sri Lanka - A.C.I.D. Karunarathne; D A C Silva (Journal of Sustainable Tourism and Entrepreneurship, 2021)
Purpose: The purpose of this study was to examine how the availability or absence of different hotel attributes affect the room rate during a given period. This study identified the impact of various hotel attributes on the room rate. Research methodology: Published data on available hotel attributes, and room rates of selected room categories of star-graded hotels in Colombo district, Sri Lanka, were gathered online through booking.com. The Ordinary Least Squares (OLS) method was used to estimate the impact of key determinants under hotel amenities, quality signals, and locational attributes. Results: The results revealed eleven key attributes of the room rate in star-graded hotels, illustrating the positive impact from seven determinants and the negative impact from four determinants. Hotel class or star grade was the most significant determinant in the room rate, which generally determines the pricing behavior and service quality and most of the attributes and characteristics in a hotel. Availability of a business center, location of the hotel, fitness center/spa, total number of rooms in the hotel, room size, and view from room also significantly determined the room rate. Limitations: Booking.com, as the most popular Online Travel Agent (OTA) used in Sri Lanka, it was assumed that the information is frequently updated. The study was extended for the hotels in the Colombo district, and hence, the results were based on the point data, which may not be an islandwide representation or year through data. Contribution: As theoretical applications are underused in pricing and revenue decisions in the Sri Lankan hotel sector, results will lead to advance the decision making of practitioners, and this study will be a complement to the lack of literature in the field of revenue management in Sri Lankan context and may encourage future researchers laying an inspiring beginning.